Tc-99m direct radiolabeling of monoclonal antibody ior egf/r3: quality control and image studies in mice - Carla Roberta Dias; Barbara Marczewski; Vanessa Moraes; Marycel Figols de Barboza; João Alberto Osso Junior (Brazilian Archives of Biology and Technology, 2005)
Monoclonal antibodies (Mabs) have been useful for immunoscintigraphic applications in clinical diagnosis since they were introduced in the practice of nuclear medicine. The ior egf/r3 (Centis, Cuba) is a murine monoclonal antibody against epidermal growth factor receptor (EGF-R) and has been widely used in the radioimmunodiagnosis of tumors of epithelial origin. Labeled with 99mTc, its main application in Nuclear Medicine is the follow up, detection and evaluation of tumor recurrences. The objective of this work is to describe the preparation of a lyophilized formulation (kit) for radiolabeling the Mab ior egf/r3 with 99mTc for immunoscintigraphic applications. Radiolabeling efficiency, effects on immunoreactivity, image studies and stability of the formulation are reported. The study demonstrated that the kit formulation can be labeled with 99mTc at high yields and can be used to visualize in vivo human tumors of epithelial origin by immunoscintigraphy studies. Anticorpos monoclonais (AcM) tem sido usado para aplicações imunocintilográficas no diagnóstico clínico desde sua introdução na prática da medicina nuclear. O ior egf/r3 (Centis, Cuba) é um anticorpo monoclonal murino contra o receptor do fator do crescimento epidérmico (EGF-R) e tem sido usado extensivamente no radioimunodiagnóstico de tumores de origem epitelial. Marcado com 99mTc sua maior aplicação em Medicina Nuclear é: acompanhamento, detecção e avaliação de recorrências tumorais. O objetivo deste trabalho é descrever a preparação da formulação liofilizada (kit) para radiomarcação do AcM ior egf/r3 com 99mTc para aplicações imunocintilográficas. A eficiência da radiomarcação, efeito sobre a imunorreatividade, estudos de imagem e estabilidade da formulação são relatados. O estudo demonstrou que a formulação do kit pode ser marcada com 99mTc com alto rendimento e pode ser usado para visualizar in vivo tumores humanos de origem epitelial por estudos imunocintilográficos.